Crystal growth control of rod-shaped ε-Fe2O3 nanocrystals. Issue 65 (29th October 2020) - Tokoro, Hiroko; Fukui, Junpei; Watanabe, Koki; Yoshikiyo, Marie; Namai, Asuka; Ohkoshi, Shin-ichi
Abstract : Crystal growth control of rod-shaped ε-Fe2 O3 nanocrystals is achieved by a synthesis based on the sol–gel technique. Abstract : Herein we report crystal growth control of rod-shaped ε-Fe2 O3 nanocrystals by developing a synthesis based on the sol–gel technique using β-FeO(OH) as a seed in the presence of a barium cation. ε-Fe2 O3 nanocrystals are obtained over a wide calcination temperature range between 800 °C and 1000 °C. A low calcination temperature (800 °C) provides an almost cubic rectangular-shaped ε-Fe2 O3 nanocrystal with an aspect ratio of 1.4, whereas a high calcination temperature (1000 °C) provides an elongated rod-shaped ε-Fe2 O3 nanocrystal with an aspect ratio of 3.3. Such systematic anisotropic growth of ε-Fe2 O3 is achieved due to the wide calcination temperature in the presence of barium cations. The surface energy and the anisotropic adsorption of barium on the surface of ε-Fe2 O3 can explain the anisotropic crystal growth of rod-shaped ε-Fe2 O3 along the crystallographic a -axis. The present work may provide important knowledge about how to control the anisotropic crystal shape of nanomaterials.